Length of marriage to pregnancy and the risk of preeclampsia - Khusnul Putri Maharani; Atika Atika; Ernawati Ernawati (Universitas Airlangga, 2019)
Objective: to analyze the relationship between the length of marriage to pregnancy with the incidence of preeclampsia.Materials and Methods: This study was an observational analytic study with case control approach. Samples were 33 respondents with preeclampsia and 66 respondents with normal pregnancy, all were primigravida with age of 20-35 years old in Dr. M. Soewandhie Hospital, Surabaya, Indonesia, in January-June 2017. Data were taken from medical record.Results: This study found that the length of marriage until pregnancy was 0-4 months with percentage of 39.4% and 77.3% for case and control group respectively. Chi-square test resulted in p = 0.00 and contingency coefficient = 0.366, which meant there was relationship between the length of marriage to pregnancy and the incidence of preeclampsia in primigravida in Dr. M. Soewandhie Hospital Surabaya from January to June 2017 despite being in low level. The value of odd ratio (OR) was 0.191 (95% CI 0.077-0.473), which means there was a risk of protection for the length of marriage to pregnancy <4 months against the incidence of preeclampsia.Conclusion: The shorter the length from early marriage to pregnancy in primigravida, the lower the risk for developing preeclampsia.